Micronutrient Assessment of Cocoa, Kola, Cashew and Coffee Plantations for Sustainable Production at Uhonmora, Edo State, Nigeria - Joseph Sunday Ogeh; Rotimi Rofus Ipinmoroti (UNIVERSITY OF LAMPUNG, 2013)
The micronutrient status of the soils and leaf of cocoa, kola, cashew and coffee plantations to study the soil-plant micronutrient content relationship in the plantation soils for proper management towards optimum production of the crops was investigated at Uhonmora, Edo State, Nigeria. Soil and leaf samples were collected from these plantations and analyzed according to standard laboratory procedures. The soil samples were analyzed for the micronutrients (Cu, Mn, Zn and Fe) and in addition pH, organic carbon, sand, silt and clay contents, while the leaves were analyzed for only the micronutrient contents. Results indicated that the soils were sandy loam, acidic, low in organic carbon, deficient in Cu and Mn but very high in Fe and Zn contents. This probably resulted in nutrient imbalance in the soils and the deficiency of the nutrients in the crops. The plantations therefore require application of organic manures and micronutrient fertilizers to rectify the inadequate soil organic matter and to supply sufficient amount of Cu and Mn in the soils, to obtain quality fruit yield at optimum level from the plantations.Keywords: Cashew, cocoa, coffee, kola, micronutrients, sustainable production [How to Cite: Ogeh JS and RR Ipinmoroti. 2013. Micronutrient Assessment of Cocoa, Kola, Cashew and Coffee Plantations for Sustainable Production at Uhonmora, Edo State, Nigeria. J Trop Soils 18 (2): 93-97. Doi: 10.5400/jts.2013.18.2.93] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.93] REFERENCESAdebiyi S, EO Uwagbue, EA Agbongiarhuoyi, I Ndagi and EO Aigbekaen. 2011. Assessment of agronomic practices among kola farmers in Osun State, Nigeria. World J Agric Sci 7: 400-403.Afolabi CA and NE Egbe. 1984. Yield response of kola to N, P and K fertilizer application: A case study of preliminary trial. Cafe Cacao The 28: 13-16. AOAC [Association of Official Analytical Chemists]. 1990. Official Methods of Analysis, 15th Edition. Washington DC: 774-784.Ayanlaja SA. 1983. Rehabilitation of cocoa (Theobroma cacao L.) in Nigeria: Major problem and possible solution. Plant Soil 73: 403-409.CBN [Central Bank of Nigeria]. 2010. Annual Report and Statement of Accounts for the year. Abuja, Nigeria. 182 p.Chude VO and GO Obigbesan. 1983. Safe and toxic application rates of boron for cocoa seedlings. Plant Soil 74: 145-147.Egbe NE, EA Ayodele and CR Obatolu. 1989. Soils and nutrition of cocoa, coffee, kola cashew and tea. Prog Tree Crop Res 2: 28-38.Falade JA. 1978. Cashew growing soil in Nigeria. East Afr Agric J 43: 100-105. FAO [Food and Agriculture Organization]. 2010. Food and Agriculture Organization of the United Nations. http://faostat.fao.org/site/567/DesktopDefault.aspx? PageID=567#ancor. Accessed on 21 January 2010.Ibiremo OS and O Fagbola. 2008. Effect of phosphorus fertilizer and arbuscular mycorhizal fungi inoculation on the growth of cashew seedlings in two soils in Nigeria. Nigerian J Soil Sci 18: 138-146.Ipinmoroti RR, OSO Akanbi, MA Daniel, LA Adebowale, GA Adewoye, EA Makinde and CO Kayode. 2011. Potentials of NPK and organic fertilizers on growth performance of cashew (Anacardium occidentale L.) seedlings on degraded typic alfisol soils in Ibadan, Nigeria. J Agric Sci Tech 1: 876-881.Ipinmoroti RR, P Aikpokpodion and OSO Akanbi. 2009. Nutritional assessment of cocoa plots for soil fertility management on some cocoa farms in Nigeria. Proceedings of 16th International Cocoa Research Conference Held at Grand Hyatt Hotel, Nusa Dua, Bali, Indonesia, pp 1481-1485.Iremiren GO and AM Ekhomun. 2005. Effects of N fertilizer rates on the performance of maize-okra mixture in an acid sand soil of the Nigerian forest zone. Nigerian J Appl Sci 23: 11-14. McKenzie RH. 2001. Micronutrient requirements of crops. Alberta Agriculture and Rural development http://www1.agric.gov.ab.ca/department/deptdocs.nsf/all/agdex713. Acessed on 21 July 2011.Nelson DW and LE Sommers. 1982. Organic carbon and soil extracts In: D L Sparks (ed). Methods of soil Analysis. Part 2- Chemical and microbiological properties. Agronomy Monograph No.9, 2nd Edition. American Society of Agronomy, Soil Science Society of America, Madison, WI, USA, pp. 539-579.Ogunlade MO, OS Ibiremo, RR Ipinmoroti, CI Iloyanomon and PE Aikpokpodion. 2011. Determination of phosphorus and potassium fixation capacities and fertilizer fctors in soils of three cocoa growing areas of Nigeria. J Soil Nat 5: 11-16.Ogunmoyela OA and CR Obatolu. 1984. Nutrient studies and fertilizer requirements of Nigeria tea. Cafe Cacao The 28: 179-184.Ogunwale JA, JO Olaniyan and MO Aduloju. 2002. Morphological, physico-chemical and clay mineralogical properties of soils overlaying basement complex rocks in Ilorin East, Nigeria. Moor J Agric Res 3: 147-154.Ojeniyi SO. 1980. Nutrient studies of NPK treated coffee plots. Plant Soil 56: 175-179.Omotoso TI. 1974. The effect of fertilizer and irrigation on the leaf macronutrient composition of Coffea canephora during a year. Turrialba 24: 315-318.Opeke LK. 1987. Tropical tree crops. Spectrum Books Limited, Ibadan, Nigeria, p 247.Wood GAR and RA Lass. 1985. Cocoa, 4th ed. London: Longman, pp. 620-632.